Where is the engineering I applied for? A longitudinal study of students' transition into higher education engineering, and their considerations of staying or leaving. (3rd March 2016) - Holmegaard, Henriette Tolstrup; Madsen, Lene Møller; Ulriksen, Lars
Abstract : This paper presents results from a qualitative longitudinal study of students' transition into higher education engineering. The study aims at comparing upper-secondary school students' expectations of engineering with their actual experiences when encountering the engineering programme. It explores how this encounter provides a platform for students to become integrated during first year. We find that students' expectations are poorly met by their first-year study programme. In their attempt to bridge the gap between their expectations and their experiences, the students apply three strategies: some endure the gap, some constantly try out different study strategies and some compromised their expectations and identities to become more aligned with the study programme. The findings show that even when students successfully manage to bridge the gap, their strategy may turn out to be counterproductive from a learning point of view. The implications of the study are discussed.